Pendukung Keputusan Penentuan Jumlah Order Menggunakan Fuzzy Mamdani - Sonalitha, Elta (MATICS, 2017)
To get customer satisfaction, a restaurant should always provide raw materials in accordance with the menu. Each raw material has a different demand based on an uncertain customer interest. Purchasing managers have difficulty in determining the number of orders for each raw material, due to the uncertainty of demand and supply. Therefore we built decision support system for determining the number of orders using fuzzy mamdani. From decision support system we get ROP and recommendation of the number of orders accompanied by the total purchase price for each raw material. This system helps the purchasing managers in determining the amount of orders quickly and precisely by considering the losses, especially in the field of financial management.